Hubungan Dukungan Keluarga Dengan Kepatuhan Perawatan Post Operasi Katarak - Dedi Krismiadi; Asbath Said; Ferti Yatna; Hasniah Dina; Apriyanti (Jurnal Keperawatan Florence Nightingale, 2026)
Cataracts occur due to clouding of the eye lens, which causes obstruction of light entering the eyeball and results in impaired vision. To prevent complications, cataract surgery is necessary. However, if postoperative cataract care is not properly managed, complications such as infection may occur. Family support plays an important role in helping maintain patients' health and accelerating the recovery process of postoperative cataract patients. This study aimed to determine the relationship between family support and treatment adherence among postoperative cataract patients at RSUD Bahteramas. This study used a quantitative research method with a cross-sectional study design. The population consisted of 1,027 patients, and the sample size in this study was determined using the Sugiyono formula, resulting in 84 respondents selected through purposive sampling technique. Statistical analysis using the chi-square test obtained a p-value of 0.000. This means that there is a significant relationship between family support and treatment adherence among postoperative cataract patients at Bahteramas Regional Hospital, Southeast Sulawesi Province. In addition, the phi coefficient (φ) value of 0.60 indicated that the relationship between family support and treatment adherence was strong. In conclusion, good family support can increase patient motivation, help remind patients to take medication, and ensure that patients follow postoperative care recommendations, thereby accelerating the healing process and preventing complications.